Multi-layer assembled DNA hydrogel and its silicification preparation method and application

CN122424124BActive Publication Date: 2026-10-27SHANDONG UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202610808133.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-06-05
Publication Date
2026-10-27
Estimated Expiration
2046-06-05

AI Technical Summary

Technical Problem

尽管上述结构在理想条件下表现优异,但其实际应用中,由于DNA纳米结构自身的稳定性高度依赖于环境的温湿度、离子强度及pH环境,且在生理环境中易遭受核酸酶的降解;此外,将DNA瓦片组装成纳米管的粘性末端解离温度,显著低于瓦片结构主体的熔解温度,导致组装体在远低于设计值的温度下即发生解离与结构坍塌,严重损害了载药体系的长期结构完整性与释药可控性

Benefits of technology

(1)通过DNA单链构成初级组装单元(瓦片结构),再进一步形成次级组装结构(纳米管),纳米管通过碱基互补配对形成三级组装结构(水凝胶),最后通过原位硅化在网络上包覆一层二氧化硅壳层。纳米管腔可用作药物分子的载体,硅化可以提高水凝胶的机械强度、热稳定性和酶抗性、调节DNA纳米管的带电性质,实现生理条件下小分子药物的控制释放。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122424124B_ABST
    Figure CN122424124B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of biological materials, and particularly relates to a multi-level assembled DNA hydrogel and a siliconized preparation method and application thereof. The hydrogel is formed by DNA single strands as primary assembly units (tiles), and then secondary assembly structures (nanotubes) are further formed. The nanotubes form a tertiary assembly structure of the hydrogel through base complementary pairing, and finally a layer of silica shell is coated on the network through in-situ siliconization. The nanotube cavity can be used as a carrier of drug molecules, and the siliconization can improve the mechanical strength and thermal stability of the hydrogel, adjust the charge properties of the DNA nanotube, and realize the controlled release of drug molecules under physiological conditions. Therefore, the application has wide application prospects in the fields of biological medical materials, biological pharmaceutical materials, molecular intelligent controlled release systems and the like as a rationally designed biological / composite nanomaterial.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of biomaterials technology, specifically relating to a multi-level assembled DNA hydrogel and its silanization preparation method and application. Background Technology

[0002] DNA nanotechnology, relying on the programmable nature of the base complementary pairing principle, can construct nanostructures with specific shapes and sizes, and further assemble them into macroscopic DNA hydrogels, which have broad application prospects in fields such as biosensing, biomaterials, controlled release of drug molecules, and drug delivery.

[0003] However, hydrogels composed solely of DNA networks have excessively large pore sizes and limited mechanical strength, making it difficult to achieve confinement and controlled release of small molecule drugs. Researchers constructed hydrogel frameworks using confined spatial structures such as hollow DNA nanotubes and extended the nanotube scale to the micrometer level using modular assembly of DNA tiles to enhance the confinement effect on small molecule diffusion. Although the above structures perform excellently under ideal conditions, in practical applications, the stability of DNA nanostructures is highly dependent on the temperature, humidity, ionic strength, and pH environment, and they are easily degraded by nucleases in physiological environments. In addition, the dissociation temperature of the viscous ends of the DNA tiles assembled into nanotubes is significantly lower than the melting temperature of the tile structure itself, causing the assembly to dissociate and collapse at temperatures far below the design value, severely compromising the long-term structural integrity and controllable drug release of the drug delivery system. Summary of the Invention

[0004] The purpose of this invention is to provide a multi-level assembled DNA hydrogel and its silanization preparation method and application, thereby overcoming the shortcomings of the prior art. By forming a conformal silica shell on the DNA template through the sol-gel method, the thermal stability, chemical stability and enzyme resistance of the DNA assembly can be significantly improved.

[0005] To achieve the above objectives, the technical solution of the present invention is as follows: In a first aspect, the present invention provides a method for preparing a multi-level assembled DNA hydrogel, comprising the following steps: adding five single strands constituting DNA tile 1 and five single strands constituting DNA tile 2 to a buffer solution, and subjecting them to a temperature-programmed annealing process to obtain primary assembly unit A and primary assembly unit B, respectively. Primary assembly unit A and primary assembly unit B were subjected to heat preservation treatment to obtain nanotube A and nanotube B, respectively. Nanotubes A and B were diluted and mixed, and then self-assembled and cross-linked to obtain a DNA hydrogel.

[0006] This method uses "tiles" Nanotubes The stepwise self-assembly of the hydrogel, combined with a magnesium ion-containing buffer solution and a specific temperature-programmed annealing process, enables the control of the hollow nanotube scale and the pore size of the hydrogel network, effectively solving the problem that traditional DNA hydrogels have difficulty retaining small molecule drugs.

[0007] Secondly, the present invention provides a multi-level assembled DNA hydrogel as described in the first aspect and a multi-level assembled silanized DNA hydrogel prepared by the silanization method thereof. The silanized DNA hydrogel possesses excellent structural integrity, controllable drug loading, and long-term cycling stability.

[0008] Thirdly, the present invention provides the application of the multi-level assembled silicified DNA hydrogel described in the second aspect in drug delivery. By utilizing the hollow lumen of the multi-level assembled silicified DNA hydrogel to load small molecule drugs and restrict their free diffusion, sustained release of small molecule drugs can be achieved.

[0009] The beneficial effects of this invention are: (1) Primary assembly units (tile structure) are formed by DNA single strands, which further form secondary assembly structures (nanotubes). The nanotubes form tertiary assembly structures (hydrogels) through complementary base pairing. Finally, a silica shell is coated on the network through in-situ silanization. The nanotube lumen can be used as a carrier for drug molecules. Silicification can improve the mechanical strength, thermal stability and enzyme resistance of the hydrogel, regulate the charged properties of DNA nanotubes, and achieve controlled release of small molecule drugs under physiological conditions.

[0010] (2) The elastic modulus limit of the multi-level assembled silicified DNA hydrogel is 10. 3 -10 4 Pa, compared to unsilicified hydrogels (10 2 -10 3 The encapsulation efficiency is related to the molecular weight, and the release rate is related to the net charge of the molecule in the solution. Attached Figure Description

[0011] The accompanying drawings, which form part of this invention, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an improper limitation of the invention.

[0012] Figure 1 This is a schematic diagram of the preparation method of the siliconized multilevel assembled DNA hydrogel in Example 1 of the present invention; S0 represents an unsiliconized DNA hydrogel, and S0.2, S0.5, S1, and S2 represent different folds of silicon reagent.

[0013] Figure 2The mechanical properties of samples S0, S0.2, S0.5, S1, and S2 obtained in this invention; Figure 3 The thermal stability of samples S0, S0.2, S0.5, S1, and S2 obtained in this invention; Figure 4 The enzyme resistance of the sample prepared in this invention to DNase I; Figure 5 To determine the release rate of the small molecule drug model of this invention at 25°C, three models were selected: cationic brilliant red (positively charged), crocin (neutral), and brilliant blue (negatively charged). a) shows a controlled release diagram, b) shows the cumulative release curve, and c) shows the time (T) required for 50% release. 50% The relationship between d) and molecular loading, where d) represents T before and after silanization. 50% The relationship between the change and molecular loading, e) is the relationship between encapsulation efficiency and molecular weight, and f) is the relationship between the change in encapsulation efficiency and molecular loading before and after silanization.

[0014] Figure 6 This is the release curve of the small molecule drug model cationic Brilliant Red at 37°C. Figure 7 The images show the morphology and elemental distribution of the DNA hydrogel prepared in this invention before and after silanization. in, Figures 4-6 In the table, S0 is the unsilicified DNA hydrogel, S1 is the hydrogel prepared in Example 1, and S0.5 is the comparative example of the 300 μM, S0.5 condition in Table 2. Detailed Implementation

[0015] Those skilled in the art will understand that the following embodiments are for illustrative purposes only and should not be construed as limiting the scope of the invention. Specific conditions not specified in the embodiments are performed under conventional conditions or conditions recommended by the manufacturer. Components whose manufacturers are not specified are all commercially available conventional products.

[0016] To address the problem of controlling the slow release of small molecule drugs in existing DNA hydrogels at physiological temperatures, this invention provides a silanized multilevel assembled DNA hydrogel, its preparation method, and its applications. The hydrogel uses DNA tile primary assembly units to form a nanotube secondary assembly structure, which is then cross-linked to form a DNA hydrogel tertiary assembly structure. Small molecule drugs are loaded into hollow lumens, restricting their free diffusion. By silanizing, the hydrogel maintains its basic morphology even at physiological temperatures, successfully creating a multilevel hydrogel material with high mechanical properties, thermal stability, and enzyme resistance.

[0017] In a first aspect, the present invention provides a method for preparing a multi-level assembled silicified DNA hydrogel, comprising the following steps: adding five single strands constituting DNA tile 1 and five single strands constituting DNA tile 2 to a buffer solution, and subjecting them to temperature-programmed annealing to obtain primary assembly unit A and primary assembly unit B, respectively. Primary assembly unit A and primary assembly unit B were subjected to heat preservation treatment to obtain nanotube A and nanotube B, respectively. Nanotubes A and B were diluted and mixed, and then self-assembled and cross-linked to obtain a DNA hydrogel. Adding a silicon source to a DNA hydrogel and initiating an in-situ hydrolysis-condensation reaction results in a multi-level assembled silicified DNA hydrogel. Simultaneously, the in-situ hydrolysis-condensation reaction using an organic-inorganic hybrid silicon source constructs a conformal silica shell without disrupting the multi-level ordered structure of DNA, significantly improving the material's thermal stability, resistance to enzymatic degradation, and mechanical strength under physiological conditions.

[0018] In some other embodiments, the five single strands that make up DNA tile 1 are T-1, T-2, TA-1, TA-2, and TA-3; The DNA tile 2 is assembled from five ssDNA strands: T-1, T-2, TB-1, TB-2, and TB-3. The sequences of T-1, T-2, TA-1, TA-2, TB-1, TB-2, TA-3, and TB-3 are shown as SEQ ID NO: 1-SEQ ID NO: 8, respectively.

[0019] This DNA tile assembly method, by sharing two boundary single strands, T-1 and T-2, ensures that different tiles have a unified and stable assembly interface and structural framework. By simply replacing the TA, different functional or response modules can be flexibly introduced into the TB series internal single strands. It combines structural rigidity, assembly controllability, functional customizability and design scalability, making it easy to achieve the co-assembly of multiple types of functional tiles and the precise construction of modular nanostructures.

[0020] In some other embodiments, the concentrations of the five single strands constituting DNA tile 1 and / or the five single strands constituting DNA tile 2 are each independently 150-5000 μM; The volume ratio of the five single strands constituting DNA tile 1 and / or the five single strands constituting DNA tile 2 is independently (0.8-1.2):(0.8-1.2):(0.8-1.2):(0.8-1.2):(0.8-1.2); preferably 1:1:1:1:1. This numerical range is beneficial for the concentration matching of each strand during assembly, avoiding excess or deficiency of one or more strands, thereby improving the efficiency of correct tile folding and complete assembly, and reducing mismatches or byproduct aggregation.

[0021] In some other embodiments, the buffer solution is a magnesium-containing TAE buffer solution; The temperature-programmed annealing process is as follows: hold at 75°C for 5 minutes, cool to 65°C, anneal to 40°C at a rate of 0.2°C / min, and then anneal to 10°C at a rate of 2°C / min.

[0022] In other embodiments, the incubation process is carried out at a temperature of 30-32°C for 40-60 hours. This incubation process facilitates the slow and orderly base pairing and structural folding of DNA single strands, improving the correct yield, structural integrity, and batch stability of DNA tiles.

[0023] In some other embodiments, the volume ratio of nanotube A to nanotube B is (0.8-1.2):(0.8-1.2); preferably 1:1. This is beneficial for matching the content of the two in the composite or co-assembled system, avoiding structural segregation, uneven assembly, or functional imbalance caused by an excess of one nanotube, thereby improving the morphological uniformity, structural stability, and performance reproducibility of the composite nanomaterial.

[0024] In some other embodiments, the silicon source includes trimethyl[3-(trimethoxysilyl)propyl]ammonium chloride and tetraethyl silicate; The amount of trimethyl[3-(trimethoxysilyl)propyl]ammonium chloride added is 0.1-50 times the molar amount of the bases in the DNA hydrogel, preferably 1-10 times the molar amount of the bases in the DNA hydrogel. This allows for continuous adjustment of the degree of silanization over a wide range, avoiding both insufficient negative charge shielding due to excessive dosage, resulting in uncontrollable rapid melting and release of the gel at 37°C, and excessive cross-linking, gel embrittlement, or hindered diffusion / release due to excessive dosage. This approach is beneficial for balancing structural stability, sustained release capability, and experimental repeatability, and facilitates targeted optimization according to different systems and application requirements.

[0025] Alternatively, the amount of tetraethyl orthosilicate added is 0.1-50 times the molar amount of the bases in the DNA hydrogel, preferably 2.5-25 times the molar amount of the bases in the DNA hydrogel.

[0026] In some other embodiments, the in-situ hydrolysis-condensation reaction is first performed by shaking and mixing at a temperature below 20°C, followed by rotational mixing at a temperature below 10°C; preferably, the shaking and mixing temperature is 15-18°C, and the rotational mixing temperature is 2-6°C. This stepwise mixing method of shaking followed by rotation helps the reagents to come into full, gentle, and uniform contact with the DNA hydrogel, promoting more uniform and controllable in-situ generation and anchoring of silicon species within the gel network, thereby improving the consistency and repeatability of silanization modification and enhancing the uniformity of the gel structure.

[0027] In a second aspect, the present invention provides a method for preparing a multi-level assembled silicified DNA hydrogel, thereby producing a multi-level assembled silicified DNA hydrogel.

[0028] In other embodiments, the multi-level assembled silicified DNA hydrogel includes a DNA hydrogel and a silica layer deposited on its surface, wherein the DNA hydrogel is a three-dimensional network structure composed of hollow nanotubes. Hollow nanotubes are formed by multi-level self-assembly of DNA tile 1 and DNA tile 2.

[0029] This structure provides a high specific surface area and abundant pores through hollow channels and a porous network, which is beneficial for the efficient encapsulation and diffusion release of small molecules / drugs. At the same time, the silica layer deposited on the surface can selectively shield the negative charge of the DNA backbone, regulate electrostatic interactions and the degree of network cross-linking, thereby preventing the unsilicified gel from melting rapidly at 37°C, achieving sustained release, and improving the mechanical / structural stability and resistance to enzyme degradation of the gel.

[0030] Thirdly, the present invention provides the application of the multi-level assembled siliconized DNA hydrogel of the second aspect in drug delivery and biosensing.

[0031] The fibers constituting the three-dimensional network of the hydrogel are constructed into hollow nanotube structures, providing a high-capacity loading space for small molecule drugs. Furthermore, the confined diffusion effect effectively delays the burst release and loss of drugs in the body fluid environment. The in-situ deposition of a silica layer hybridizes and enhances the DNA network, significantly improving the elastic modulus and sol-gel transition temperature of the hydrogel. This greatly enhances its mechanical strength while endowing the material with excellent environmental stability.

[0032] The following is a further explanation with reference to specific embodiments and comparative examples: Example 1 A multi-level assembled DNA hydrogel and its silanization preparation method, such as Figure 1 As shown, the specific steps include: 1) Preparation of primary assembly units (tiles) a. Provide single-stranded DNA (ssDNA) stock solution: DNA tile 1 is assembled from five ssDNA strands: T-1, T-2, TA-1, TA-2, and TA-3; DNA tile 2 is assembled from five ssDNA strands: T-1, T-2, TB-1, TB-2, and TB-3. The DNA sequences that make up the two types of tiles (DNA tile 1 and DNA tile 2) are shown in Table 1 below.

[0033] Table 1. DNA sequences of the two types of tiles

[0034] 1b. The DNA single strands required for the two types of tile structures were mixed separately, and TAE buffer containing magnesium ions was added. After temperature programming, two primary assembly units for DNA tiles were obtained. Specifically, 1.8 μL of the stock solution of the five corresponding DNA single strands at a concentration of 5000 μM was taken, and 1.2 μL of 10×TAE-125 mM MgCl2 buffer and 1.8 μL of sterile water were added to obtain a 12 μL mixed solution. The solution was heated to 75°C and incubated for 5 minutes, then cooled to 65°C. Annealing was then carried out from 65°C to 40°C at a rate of 0.2°C / min, and then from 40°C to 10°C at a rate of 2°C / min, forming DNA tile 1 and DNA tile 2 solutions. The solution was then heated to 32°C. DNA nanotube 1 and DNA nanotube 2 were obtained by incubating at C for 48 h. They were diluted to 30 μL with 1×TAE buffer and mixed with equal volumes to obtain a multi-level assembled DNA hydrogel with a final concentration of 300 μM.

[0035] The nanotubes were diluted to 25.5 μL with 1×TAE buffer and thoroughly mixed to obtain a multilevel assembled DNA hydrogel. 9 μL of a mixture of TMAPs and TEOS (molar ratio 5:12.5) was added, and the mixture was incubated at 18°C. After thoroughly mixing by shaking at C, place it on a rotary mixer. After reacting at C for 4 hours, a multi-level assembled silanized DNA hydrogel was obtained, with a final concentration of 300 μM.

[0036] 2) Preparation of secondary assembly structures (nanotubes): Two primary assembly units were incubated at 32℃ for a certain period of time (48 hours) to obtain nanotube secondary assembly structures. Specifically, DNA tile 1 primary assembly unit and DNA tile 2 primary assembly unit were incubated at 32℃ for a certain period of time (48 hours) to obtain nanotube secondary assembly structure 1 and nanotube secondary assembly structure 2.

[0037] 3) Preparation of the tertiary assembly structure (hydrogel): The two types of nanotubes were diluted 2.5 times with 1×TAE buffer and mixed uniformly at a volume ratio of 1:1 to obtain the hydrogel tertiary assembly structure. 4) Preparation of silanized DNA hydrogel: Trimethyl[3]methyl[4]methyl[5]methyl[6]methyl[7]methyl[8]methyl[9]methyl

[10] methyl

[20] methyl[3 ... [(trimethoxysilyl)propyl]ammonium chloride (N-trimethoxysilylpropyl-N,N,N-trimethylammoniμM chloride, TMAPS) and tetraethyl orthosilicate (TEOS) were mixed by shaking at 18°C, followed by […]. C was slowly rotated and mixed to obtain a silanized DNA hydrogel (final concentration 300 μM, molar ratio of base: trimethyl[3-(trimethoxysilyl)propyl]ammonium chloride: tetraethyl silicate 1:5:12.5).

[0038] Example 2 Unlike Example 1, the concentration of tile units in the hydrogel (150-350 μM), the molar ratio of bases, trimethyl[3-(trimethoxysilyl)propyl]ammonium chloride, and tetraethyl silicate in the silanized DNA hydrogel were optimized, involving a total of 25 sets of experiments. Specifically, the concentration of tile units in the hydrogel was set to 150, 200, 250, 300, and 350 μM, respectively; the molar ratio of bases, trimethyl[3-(trimethoxysilyl)propyl]ammonium chloride, and tetraethyl silicate in the silanized DNA hydrogel was optimized. S0 represents the unsilanized DNA hydrogel. In S0.2, the molar ratio of base: trimethyl[3-(trimethoxysilyl)propyl]ammonium chloride: tetraethyl silicate is 1:1:2.5; In S0.5, the molar ratio of base trimethyl[3-(trimethoxysilyl)propyl]ammonium chloride to tetraethyl silicate is 1:2.5:6.25. In S1, the molar ratio of bases: trimethyl[3-(trimethoxysilyl)propyl]ammonium chloride: tetraethyl silicate is 1:5:12.5; In S2, the molar ratio of base: trimethyl[3-(trimethoxysilyl)propyl]ammonium chloride: tetraethyl silicate is 1:10:25.

[0039] Among them, the sample prepared when the concentration of tile units in the hydrogel is 300 μM and the molar ratio of bases, trimethyl[3-(trimethoxysilyl)propyl]ammonium chloride, and tetraethyl silicate in the silanized DNA hydrogel is 1:5:12.5 (S1) is Example 1, and the remaining 24 samples are Example 2.

[0040] The elastic modulus and sol-gel transition temperature of the samples obtained in Examples 1-2 are shown in Table 2 below.

[0041] Table 2 shows the elastic modulus and sol-gel transition temperature of the samples obtained in Examples 1-2.

[0042] In Table 2, NaN is short for Not a Number, indicating that a valid value could not be obtained.

[0043] Performance testing: Rheological tests were performed on a Kinexus Prime pro+ rheometer (Netzsch). Four types of rheological experiments were conducted: I) time-scan tests at 15 °C for 5 minutes at a fixed frequency and strain of 1 Hz and 1%, respectively; ii) frequency scans of the hydrogel between 0.1 and 100 Hz at a fixed strain of 15 °C and 1%; iii) temperature-scan tests at a fixed frequency of 1 Hz and a fixed strain of 1%, with a heating rate of 2 °C / min. The mechanical properties of the hydrogel were evaluated using the resulting storage modulus (G'), and the thermal stability of the hydrogel was evaluated using the sol-gel transition point.

[0044] DNase I was purchased from New England Biolabs and treated with 1×TAE-5 mM Mg 2+ Dilute to 100 U / mL with buffer. Immerse the (silicified) DNA hydrogel (300 μM, 60 μL, S1) in 100 μL DNase I and incubate at room temperature for 2, 6, 12, and 24 hours. As a control, immerse the hydrogel in 100 μL of 1×TAE-5 mM MgSO4. 2+ The samples were placed in buffer solution and kept for the same amount of time. Then, the samples were analyzed by rheological tests according to the above protocol.

[0045] The content of the small molecule drug model in the solution was determined by ultraviolet-visible spectroscopy, and the encapsulation efficiency was determined by the content in the rinsing solution. The cumulative release at different times was measured, and the release curve was obtained by fitting. The time required for half of the release (T) was then calculated. 50% Assess the release rate.

[0046] Depend on Figure 2 It can be seen that the silanization effect of hydrogel phase materials exhibits a clear concentration dependence. Effective silanization cannot be achieved at hydrogel concentrations below 200 μM, instead resulting in the formation of a white precipitate. Notably, a DNA hydrogel network has already formed at 200 μM, while DNA nanotubes have not gelled at 150 μM.

[0047] Unlike previous studies on the silanization of DNA nanostructures in dilute solutions, increasing DNA concentration leads to a corresponding increase in silicon reagent concentration, creating localized silica concentrations suitable for spontaneous nucleation and resulting in uncontrolled particle formation and random aggregation. However, in the presence of a hydrogel network, DNA provides abundant interfacial area for silica growth. Ultimately, the silanization effect is determined by the competition between spontaneous silica nucleation and growth along the hydrogel network interface. Only when the network is sufficiently dense (concentration greater than 250 μM) can the gel maintain silica deposition without structural collapse.

[0048] The changes in the G' and sol-gel points of the hydrogel also reflect this competitive mechanism. At 250 μM, the hydrogel stiffness begins to decrease rapidly at S1 and loses its sol-gel transition point at S2, indicating severe disruption of the internal cross-linking network. In contrast, at higher DNA concentrations (300 and 350 μM), the S1 condition produces the best overall performance because the denser network provides a more stable interface, allowing the silica layer to enhance rather than destroy the DNA hydrogel.

[0049] It is worth noting that in previous studies, the silanization of DNA nanostructures in dilute solutions typically required Mg 2+ The concentration was below 3 mM to allow trimethyl[3-(trimethoxysilyl)propyl]ammonium chloride to be effectively adsorbed onto the DNA surface. For DNA hydrogels, however, we found that higher Mg concentrations were necessary. 2+ A higher concentration (5 mM) improves reproducibility. Higher concentrations of Mg... 2+ By effectively shielding the negative charge of the phosphate backbone, the interactions between DNA duplexes are enhanced, thereby strengthening the integrity of the nanotubes and the hydrogel network assembled from them. Reacting at 4°C further enhances base-pair hydrogen bonding, leading to a similar stabilizing effect. Simultaneously, in the Stöber method, the low temperature slows down the nucleation and growth kinetics of silica, facilitating more uniform deposition along the DNA template and promoting the formation of a homogeneous and mechanically robust hydrogel network.

[0050] The significant increase in G' after silanization is attributed to the transformation of the hydrogel framework from a weakly linked DNA network to a strongly linked organic-inorganic complex. In unsilanized DNA hydrogels, elasticity is controlled by the reversible crosslinking and entropic elasticity of semi-flexible nanotubes, resulting in a relatively low effective crosslinking density and significant stress relaxation. After silanization, covalent Si–O–Si / Si–O–P bonds harden individual nanotubes and introduce additional intertube connections. Therefore, although network rearrangement reduces the crosslinking density, the increased network stiffness and reduced stress relaxation together lead to a higher G'.

[0051] In addition to increasing mechanical strength, silicification also improves the thermal stability of hydrogels. Figure 3This is mainly because the silicon shell makes the DNA double helix more difficult to unwind.

[0052] The elastic modulus of the silanized DNA hydrogel of this invention is significantly improved, by an order of magnitude under preferred conditions. The sol-gel transition temperature of the silanized DNA hydrogel of this invention is increased by approximately 8-15°C.

[0053] The silanized and non-silanized hydrogels prepared in Example 1 and Comparative Example 1 were exposed to DNase I solution at room temperature and allowed to stand for 2, 6, 12, and 24 hours, respectively. The degree of enzyme degradation was reflected by the change in G'. Figure 4 As shown, after 2 hours of reaction, the G' of the unsilicified hydrogel decreased from hundreds of Pa to less than 10 Pa, demonstrating that DNA degraded within 2 hours. In contrast, the G' of the silicified hydrogel showed almost no change after 24 hours, indicating a significant increase in enzyme resistance.

[0054] Depend on Figure 7 The morphology of the DNA hydrogel before and after silanization shows that the hydrogel has a relatively uniform network structure. The elemental distribution diagram shows that Si and P elements are distributed in a consistent manner, and the silica shell is conformally deposited on the DNA template.

[0055] Application Example 1 The sample from Example 1 was used as a carrier. Cationic Brilliant Red, Crocin, and Brilliant Blue were dissolved in 1×TAE buffer as small molecule drug models and added to the prepared DNA hydrogel at a concentration of 10 mM. The mixture was allowed to stand for 24 hours to fully load the DNA, followed by silanization.

[0056] Hydrogels containing drug models were rinsed with 1×TAE-5 mM magnesium chloride buffer to remove unencapsulated pigments. Pigment content was determined using UV-Vis spectroscopy to obtain the encapsulation efficiency (EN%). Each hydrogel was immersed in 1 mL of 1×TAE-5 mM magnesium chloride buffer at 25°C and 37°C, respectively. At predetermined time points, 2 μL samples were collected, and pigment content was determined using ultra-micro UV-Vis spectroscopy. An equal volume of fresh 1×TAE-5 mM MgCl2 buffer was added to maintain release conditions. The drug concentration in the collected aliquots was quantified using calibration curves obtained from serially diluted standards. Cumulative release was expressed as a percentage of the experimentally determined initial load. Release kinetics were evaluated by fitting the cumulative release curves to the established model.

[0057] DNA nanotubes have well-defined hollow cavities that can accommodate small molecules, making them suitable as carriers for drug loading and responsive release. For example... Figure 5As shown in a), the presence of the nanotube wall causes the model molecules to be released only from the port, theoretically reducing the diffusion coefficient of the molecules by 59%. In addition, since the DNA phosphate backbone is negatively charged, the release kinetics of small molecules are related to their charged properties in aqueous solution.

[0058] During drug release, the system undergoes structural evolution, including swelling of the DNA hydrogel and relaxation of the DNA nanotubes. For the three drug models, the release curves exhibit a distinct S-shape in the initial stage (e.g., Figure 5 As shown in b), the non-Fickian migration process involves coupled diffusion and carrier relaxation. Therefore, the Weibull model is used to fit the release kinetics. In the later stages, as swelling and structural relaxation approach equilibrium, the release behavior becomes independent of the carrier's structural changes and is primarily controlled by the concentration gradient between the hydrogel and the surrounding medium. Within this range, the release curves can be well fitted by a first-order kinetic model.

[0059] The time required to use a model that releases 50% of the drug load (T) 50% ) as a characteristic parameter to quantitatively assess the release rate (e.g. Figure 5 (as shown in c)). Small molecule drug models showed an advantage in terms of sustained release time. In non-silicified hydrogels, cationic bright red, crocin, and brilliant blue T... 50% The durations were 34.5h, 17.5h, and 11h, respectively. (T) 50% The release kinetics were positively correlated with the net molecular charge: positively charged molecules electrostatically adsorbed onto the negatively charged DNA backbone, exhibiting the longest release time, while negatively charged molecules released the fastest due to electrostatic repulsion, and neutral molecules showed a moderate release rate. Silicated DNA hydrogels further modulated the release kinetics. The transformation of the material from a purely organic DNA network to an organic-inorganic composite material reduced the intrinsic affinity between the DNA nanotubes and the encapsulated organic molecules, generally leading to accelerated release. Simultaneously, the silica shell partially shielded the electrostatic interactions of the DNA backbone, thus having a significant charge-dependent effect on the release behavior. For the positively charged cationic brilliant red, silanization weakened electrostatic attraction, thereby accelerating drug release. Conversely, for the negatively charged brilliant blue, silanization weakened electrostatic repulsion, leading to slower release, which can be observed from the T values ​​before and after silanization. 50% This has been confirmed by the changes (e.g.) Figure 5 (as shown in d)

[0060] There is a significant negative correlation between encapsulation efficiency (EN) and molecular weight; the encapsulation efficiency decreases with increasing molecular weight. Figure 5 (e) This trend can be attributed to the finite volume of the nanotube lumen, within which the number of molecules accommodated is inversely proportional to the molecular size. After silicification, the growth of the silica shell leads to a reduction in lumen volume and a decrease in encapsulation efficiency (e.g., ...). Figure 5 (as shown in f). The change in encapsulation efficiency is positively correlated with the net charge because, in addition to molecules that diffuse freely within the nanotube lumen, some pigments are adsorbed onto the negatively charged DNA backbone via electrostatic adsorption (positively charged cationic brilliant red) or other weak interactions (neutral scrocin). During silanization, these pre-bound molecules may be encapsulated in a silicon shell along with the DNA template. In contrast, the negatively charged brilliant blue is electrostatically repelled from the DNA backbone, thus exhibiting minimal interfacial binding and resulting in a greater reduction in encapsulation efficiency compared to other molecules.

[0061] These results demonstrate that silicification provides an effective method for modulating drug release kinetics in DNA-based hydrogels by simultaneously altering organic-inorganic properties and electrostatic interactions. This dual modulation enables fine-grained control over the release behavior of molecules with different charge states.

[0062] It exhibited the longest T in the release experiment. 50% Basic Red 14 (34.5 h) was selected as a representative model to demonstrate the superior performance of silanized hydrogels at higher temperatures. Figure 6 The differences in release kinetics of unsilanized, S0.5, and S1 silanized DNA hydrogels at 37 °C were shown. C, the unsilicified hydrogel melts immediately within 30 minutes, while the S1 hydrogel can achieve continuous release; T 50% This can last up to 3 hours, which demonstrates a substantial improvement in thermal stability and release control.

[0063] Since the S0.5 and S1 hydrogels did not reach swelling equilibrium within the experimental time, structural evolution occurred throughout the release process, and the release kinetics deviated from simple diffusion-controlled behavior. This can be well described by the Weibull model over the entire time range. (The release behavior at 25℃ is compared with the release behavior at T...) 50% Compared to approximately 10 hours, the response time at 37°C was reduced to approximately 3 hours, a reduction of more than three times. Although the increased temperature enhanced molecular diffusion by increasing thermal motion and reducing solvent viscosity, the significant acceleration of release was primarily attributed to the reduced electrostatic adsorption between cationic bright red and DNA nanotubes.

[0064] The above are merely preferred embodiments of the present invention and are not intended to limit the present invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A method for preparing a multi-level assembled DNA hydrogel, characterized in that, Includes the following steps: The single-stranded DNA that makes up DNA tile 1 and the single-stranded DNA that makes up DNA tile 2 are added to buffer solution and annealed at a temperature program to obtain primary assembly unit A and primary assembly unit B, respectively. Primary assembly unit A and primary assembly unit B were subjected to heat preservation treatment to obtain nanotube A and nanotube B, respectively. Nanotubes A and B are diluted and mixed, and then self-assembled and cross-linked to form a multi-level assembled DNA hydrogel. The five single strands that make up DNA tile 1 are T-1, T-2, TA-1, TA-2, and TA-3; The five single strands that make up DNA tile 2 are T-1, T-2, TB-1, TB-2, and TB-3; The sequences of T-1, T-2, TA-1, TA-2, TB-1, TB-2, TA-3, and TB-3 are shown as SEQ ID NO: 1-SEQ ID NO: 8, respectively.

2. A method for preparing a multi-level assembled silicified DNA hydrogel, characterized in that, The multi-level assembled DNA hydrogel prepared by the preparation method according to claim 1 is mixed with a silicon source and subjected to in-situ hydrolysis and condensation reaction to prepare a multi-level assembled silicified DNA hydrogel.

3. The method for preparing the multi-level assembled DNA hydrogel as described in claim 1, characterized in that, The concentrations of the five single strands constituting DNA tile 1 and / or the five single strands constituting DNA tile 2 are each independently 150-5000 μM; The volume ratio of the five single strands constituting DNA tile 1 and / or the five single strands constituting DNA tile 2 is independently (0.8-1.2):(0.8-1.2):(0.8-1.2):(0.8-1.2):(0.8-1.2).

4. The method for preparing the multi-level assembled DNA hydrogel as described in claim 3, characterized in that, The volume ratio of the five single strands constituting DNA tile 1 and / or the five single strands constituting DNA tile 2 is independently 1:1:1:1:

1.

5. The method for preparing the multi-level assembled DNA hydrogel as described in claim 1, characterized in that, The buffer solution is a magnesium-containing TAE buffer solution; The temperature-programmed annealing process is as follows: hold at 70-80℃ for 1-10 min, cool to 60-65℃, anneal at a rate of 0.1-0.5℃ / min to 35-45℃, and then anneal at a rate of 1-5℃ / min to 5-15℃.

6. The method for preparing the multi-level assembled DNA hydrogel as described in claim 5, characterized in that, The temperature-programmed annealing process is as follows: hold at 75°C for 5 minutes, cool to 65°C, anneal to 40°C at a rate of 0.2°C / min, and then anneal to 10°C at a rate of 2°C / min.

7. The method for preparing the multi-level assembled DNA hydrogel as described in claim 1, characterized in that, The heat preservation treatment is carried out at a temperature of 30-32℃ for a duration of 40-60 hours. The volume ratio of nanotube A to nanotube B is (0.8-1.2):(0.8-1.2).

8. The method for preparing the multi-level assembled DNA hydrogel as described in claim 7, characterized in that, The volume ratio of nanotube A to nanotube B is 1:

1.

9. The method for preparing the multi-level assembled silicified DNA hydrogel as described in claim 2, characterized in that, The silicon source includes trimethyl[3-(trimethoxysilyl)propyl]ammonium chloride and tetraethyl silicate; The amount of trimethyl[3-(trimethoxysilyl)propyl]ammonium chloride added is 0.1-50 times the molar amount of the bases in the DNA hydrogel. Alternatively, the amount of tetraethyl orthosilicate added is 0.1-50 times the molar amount of the bases in the DNA hydrogel.

10. The method for preparing the multi-level assembled silicified DNA hydrogel as described in claim 9, characterized in that, The amount of trimethyl[3-(trimethoxysilyl)propyl]ammonium chloride added is 1-10 times the molar amount of the bases in the DNA hydrogel.

11. The method for preparing the multi-level assembled silicified DNA hydrogel as described in claim 9, characterized in that, The amount of tetraethyl orthosilicate added is 2.5-25 times the molar amount of the bases in the DNA hydrogel.

12. The method for preparing the multi-level assembled silicified DNA hydrogel as described in claim 2, characterized in that, The in-situ hydrolysis-condensation reaction is first mixed by shaking at a temperature below 20°C, and then mixed by rotating at a temperature below 10°C.

13. The method for preparing the multi-level assembled silicified DNA hydrogel as described in claim 12, characterized in that, The temperature for oscillation mixing is 15-18℃, and the temperature for rotation mixing is 2-6℃.

14. A multi-level assembled DNA hydrogel prepared by the method of preparing a multi-level assembled DNA hydrogel according to any one of claims 1, 3-8, and a multi-level assembled silanized DNA hydrogel prepared by the method of preparing a multi-level assembled silanized DNA hydrogel according to any one of claims 2, 9-13.

Citation Information

Patent Citations

  • Controllable degradation silicified DNA hydrogel as well as preparation method and application thereof

    CN120590649A